Archaeological theory in a nutshell - Praetzellis, Adrian 1952- (Left Coast Press Inc., 2015)
"Adrian Praetzellis provides a brief, readable introduction to contemporary theoretical models used in archaeology for the undergraduate or beginning graduate student. He demystifies a dozen flavors of contemporary theory for the theory-phobic reader, providing a short history of each, its application in archaeology, and an example of its use in recent work. The book teaches about different contemporary archaeological theories including postcolonialism, neoevolutionism, materiality, and queer theory; is written in accessible language with key examples for each theory; includes illustrations and cartoons by the author; and provides questions at the end of each chapter to facilitate discussion"